The Racial Tensions Depicted in Lorraine Hansberry’s A Raisin in the Sun - BALOG, PERSIEUS (International Journal of Arts, Sciences and Education, 2022)
Lorraine Hansberry’s A Raisin in the Sun is considered to be one of the significant dramas written by an African American. This play depicts the racial tensions that happened on micro and macro levels during the 1950s and 1960s in the Black American community. In this regard, this paper investigates the different layers of racism and ways how the characters fit into the concept of affluent domesticity in a local and national sense. The study reveals that racism happens at the micro-level because of other members of African American community. Based on the analysis George and Asagai became the oppressor of other characters in the story. Although both of them represent two different extremes – assimilation and Afrocentrism, their actions and values in life still resorted to the oppression of other members of the black community. Moreover, the racism at the macro level revolves around segregation in housing and job opportunities. These social issues are some of the main reasons why black Americans suffered greatly in the 1950s and 1960s. In addition, the pursuit of American identity and the American dream is also highlighted in the drama through the aspirations of the main characters in the play.